2019
DOI: 10.1109/access.2019.2949357
|View full text |Cite
|
Sign up to set email alerts
|

SOC Oriented Electrochemical-Thermal Coupled Modeling for Lithium-Ion Battery

Abstract: This paper proposes an electrochemical-thermal coupling model for state of charge (SOC) estimation of lithium-ion batteries (LIBs). In this paper, to solve two numerical problems in the quasi twodimensional model of LIBs, a simplified one-dimensional model is built. Considering that the parameters in the model are affected by temperature, the internal parameters of the battery which obey the Arrhenius equation are introduced. Based on the simplified one-dimensional model, the electrochemical-thermal coupling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Heat transfer considers the transfer and distribution of heat within the battery, while heat generation considers the heat generated by chemical reactions within the battery. 80 The thermal model can accurately estimate and predict the temperature distribution and thermal characteristics of LIBs, which is helpful to improve the performance and safety of batteries. 81 It can also help optimize the design and control strategies of battery systems and improve battery life and performance.…”
Section: Analysis Of Various Modeling Methods Of Libsmentioning
confidence: 99%
“…Heat transfer considers the transfer and distribution of heat within the battery, while heat generation considers the heat generated by chemical reactions within the battery. 80 The thermal model can accurately estimate and predict the temperature distribution and thermal characteristics of LIBs, which is helpful to improve the performance and safety of batteries. 81 It can also help optimize the design and control strategies of battery systems and improve battery life and performance.…”
Section: Analysis Of Various Modeling Methods Of Libsmentioning
confidence: 99%
“…Arrhenius equation governs the most significant temperaturedependent parameters including diffusion coefficient and electrolyte ionic conductivity. So, the diffusion coefficient under the discharge process can be described as [14]…”
Section: Thermal Dependent Parametersmentioning
confidence: 99%
“…Resistance and OCV also follow Arrhenius equation. And because the effect of temperature to them is relatively minor, R (T ) and V oc (T ) can be simplified as linear equation [14]…”
Section: Thermal Dependent Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al developed an advanced model to couple the electrochemical-thermal effect for the state of charge estimation of lithium-ion batteries. The results showed that the model could effectively evaluate the state of charge [8]. Zhou, Li and Xie proposed a systematic fastmodelling approach to numerically investigate the thermal effect's impact on battery performances [9].…”
Section: Introductionmentioning
confidence: 99%